Respuesta :
[tex]n^2-2n-3=0[/tex] , (-2n = n - 3n)
[tex]n^2+n-3n-3=0\\\\ n(n+1)-3(n+1)=0\\\\ (n+1)(n-3)=0\\\\ n+1=0 \ \vee \ n-3=0\\\\ n=-1 \vee n=3[/tex]
2)
[tex]n^2-2n-3=0\\\\ (n^2-2n+1)-1-3=\\\\ (n-1)^2-4=0\\\\ (n-1)^2=4\\\\ (n-1)^2=2^2\ |()^{\frac{1}{2}}\\\\|n-1|=2\\\\n-1=2\ or \ n-1=-2\\\\n=2+1 \ or \ n=1-2\\\\ n=3 \ or \ n=-1[/tex]
[tex]n^2+n-3n-3=0\\\\ n(n+1)-3(n+1)=0\\\\ (n+1)(n-3)=0\\\\ n+1=0 \ \vee \ n-3=0\\\\ n=-1 \vee n=3[/tex]
2)
[tex]n^2-2n-3=0\\\\ (n^2-2n+1)-1-3=\\\\ (n-1)^2-4=0\\\\ (n-1)^2=4\\\\ (n-1)^2=2^2\ |()^{\frac{1}{2}}\\\\|n-1|=2\\\\n-1=2\ or \ n-1=-2\\\\n=2+1 \ or \ n=1-2\\\\ n=3 \ or \ n=-1[/tex]